Isolation, evaluation and characterization of isolated compounds from aqueous extract of Cestrum nocturnum - Chandra Kishore Tyagi,; Deenanath Jhade,; Sunil Kumar Shah, (International Journal of Phytomedicine, 2016)
The aim of present study was to isolate, characeterise and evaluation anticoagulant properties of the isolated compound from aqueous extract of Cestrum nocturnum using aPTT-Activated Partial Thromboplastin Time, PT- Prothrombin Time & TT-Thrombin Time as standard procedures. From all the result it can be concluded that water extract of Cestrum nocturnumplant was found to be best among all the extract under study and from the isolates of water extract of Cestrum nocturnum plant AE5 was found to be best activity (anti-platelet, Fibrinolytic and anti-coagulant). Further fractionation of water extract generated two isolates AE5a & AE6a and after their pharmacological activity they were found to be potent phytochemical constituents. From the structural elucidation study of AE5a & AE6a were identified as Rutin and quercetin respectively. From this study it was concluded that the flavoinoidal compound i.e. Rutin and Quercetin were present in the Cestrum nocturnum plant and they both responsible for the anti-platelet, Fibrinolytic and anticoagulamt activity of plant.